PERANCANGAN SISTEM PENJADWALAN DAN PENGGAJIAN KARYAWAN TOKO KEBAYA AMORA BERBASIS WEB METODE EXTREME PROGRAMMING: PERANCANGAN SISTEM PENJADWALAN DAN PENGGAJIAN KARYAWAN TOKO KEBAYA AMORA BERBASIS WEB METODE EXTREME PROGRAMMING - Muhammad Anis; Diky Syafitra (JUPIK : Jurnal Penelitian Ilmu komputer, 2025)
Amora kebya is one of the business units located in South Jakarta, Amora kebaya often experiences problems during the attendance and payroll process. Starting from errors during employee attendance to errors when calculating employee salaries because the system is still manual. Other obstacles also occur in the management of data supporting the attendance and payroll system which is still managed manually so that there is no special database that connects these data for easy data access. The purpose of this research is to design and build Amora kebaya Attendance and Payroll Information System using PHP and MySql. This research is made using the extreme programming software development method which includes planning, design, coding and testing stages. The result of this research is an attendance and payroll information system that is made using extreme programming as a programming language and has features of managing employee data, position data, shift data, basic salary data, attendance data, payroll data and print payroll reports and salary slips so as to optimize the attendance process and payroll reports that have not been computerized properly to be better and can minimize errors that occur. Keywords: Attendance and payroll information system, amora kebaya, Extreme Programming, PHP, MySQL.